Utilizing Hip Abduction Strength to Body-Weight Ratios in Return to Sport Decision-Making After ACL Reconstruction - Steven Higbie; Jacquelyn Kleihege; Brian Duncan; Walter R. Lowe; Lane Bailey (International Journal of Sports Physical Therapy)
# Background